Extreme Climbing - Crossingham, John; Kalman, Bobbie (New York : Crabtree Pub., 2004)
This book describes styles of climbing, such as traditional climbing, sport climbing, and bouldering; equipment used by climbers; and annual competitions for athletes from around the world.
Includes index.
Includes glossary.
4-8
Accelerated Reader AR
Keywords: Mountaineering; Extreme sports